Influence of diet on assimilation and turnover of C-13 in the tissues of broiler chickens - Cruz, V. C.; Ducatti, Carlos [UNESP]; Pezzato, Antonio Celso [UNESP]; Pinheiro, D. F.; Sartori, José Roberto [UNESP]; Goncalves, J. C.; Carrijo, A. S. (Taylor & Francis Ltd, 2005)
1. The C-13 turnover rates of the liver and thoracic pectoral muscle of growing broilers were determined by feeding diets with varying C-13 content.2. Male chicks ( 1- d- old) were subjected to treatments based on free choice of 5 different mixes of energy and protein sources from plants with C-3 and C-4 photosynthetic pathways that had differing C-13 content. Rice bran ( R) and soybean meal ( S) were the C-3 sources, while maize ( C) and maize gluten meal ( G) were the C-4 sources. Choices were R + S, C + G, R + G, C + S or R + C +G + S. The 6th treatment was a complete feed ( CF) that was similar to a commercial broiler feed.3. The isotopic composition of the birds' tissues was representative of the isotopic composition of the diets. The assimilation was faster for C-3, in both liver and muscle, than for C-4 diets, and give the delta per mil difference between the diet and tissues.4. The liver is the most active metabolic tissue and gave more rapid isotope turnover than in muscle.